Nomenclatural notes on Indian Calamus (Arecaceae) - V. B., Sreekumar; Henderson, Andrew (Phytotaxa, 2014)
Several changes are proposed for Indian species of Calamus: C. basui is placed in synonymy under C. baratangensis; C. delessertianus is placed in synonymy under C. tenuis; C. dransfieldii, C. lacciferus, C. neelagiricus, C. prasinus, C. renukae, and C. shendurunii are considered members of a species complex and are placed in synonymy under C. gamblei; C. nicobaricus is placed in synonymy under C. pseudorivalis; C. pseudofeanus is shown to be based on a mixed collection and is placed in synonymy under C. vattayila; C. travancoricus is placed in synonymy under C. rheedei; and C. semierectus is placed in synonymy under C. andamanicus.